The Presentation Of Imagery And Expressive Means In Artistic Translation On The Example Of Yu Hua’s Novel "To Live" - Qosimova, Gulchehra (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
To reveal the artistic expression of human dignity, patience and historical tragedies in the work. Comparative literary, historical and psychologic his article analyzes Yu Hua’s novel "To Live". The purpose of the study is to al methods are used in the analysis. The results show that the novel leads from a personal tragedy to a universal philosophical conclusion and proposes that life itself is the highest value. In the process of research, the original text of the work and its Uzbek translation are analyzed comparatively, paying attention to the extent to which such arts as simile, animation and closed analogy (allusion) are preserved in the translation. The article substantiates that the priority task in translation is not only literal correspondence, but also the transmission of content and artistic spirit. In conclusion, it is emphasized that the Uzbek translation adequately reflects the artistic and aesthetic value of the work